Jervis Bay Nature Reserve : draft development and management plan - Australia. Department of the Capital Territory (Canberra : Australian Govt. Pub. Service, 1979)
Development of nature reserve; zoning; environmental management; Wreck Bay settlement.
Australian Govt. Pub. Service cat. no.797058X.
Bibliography: p. 48-49.
Keywords: Nature reserves. New South Wales. Jervis Bay. Jervis Bay Nature Reserve. Proposals; National parks and reserves -- Australian Capital Territory; Habitation - Crisis accommodation; Jervis Bay National Park (A.C.T.); Jervis Bay (ACT / NSW S Coast SI56-13); Wreck Bay (ACT / NSW S Coast SI56-13)